Managing the radio spectrum : framework for reform in developing countries - Wellenius, Björn (The World Bank, 2008)
Bringing management of the radio spectrum closer to markets is long overdue. The radio spectrum is a major component of the infrastructure that underpins the information society. Spectrum management, however, has not kept up with major changes in technology, business practice, and economic policy that have taken place worldwide during the last two decades. For many years traditional government administration of the spectrum worked reasonably well, but more recently it has led to growing technical and economic inefficiencies as well as obstacles to technological innovation. Two alternative approaches to spectrum management are being tried in several countries, one driven by the market (tradable spectrum rights) and another driven by technology innovation (spectrum commons). This paper discusses the basic features, advantages and limitations, scope of application, and requirements for implementation of these three approaches. The paper then discusses how these approaches can be made to work under conditions that typically prevail in developing countries, including weak rule of law, limited markets, and constrained fiscal space. Although spectrum reform strategies for individual countries must be developed case by case, several broadly applicable strategic options are outlined. The paper proposes a phased approach to addressing spectrum reform in a country. It ends by discussing aspects of institutional design, managing the transition, and addressing high-level changes such as the transition to digital television, the path to third-generation mobile services, launching of wireless fixed broadband services, and releasing military spectrum. The paper is extensively annotated and referenced